2011
DOI: 10.1371/journal.pone.0025458
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characteristics Reveal Neural Stem Cell Differentiation Potential

Abstract: BackgroundDistinguishing human neural stem/progenitor cell (huNSPC) populations that will predominantly generate neurons from those that produce glia is currently hampered by a lack of sufficient cell type-specific surface markers predictive of fate potential. This limits investigation of lineage-biased progenitors and their potential use as therapeutic agents. A live-cell biophysical and label-free measure of fate potential would solve this problem by obviating the need for specific cell surface markers.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 54 publications
9
109
0
Order By: Relevance
“…The change in capacitance could also be related to changes in the permittivity of the membrane due to the action of 4-MU in shortening the HA chains; however, we suggest that of the two mechanisms, the effects of morphology charge are likely to significantly outweigh those of permittivity change. The unique differences in the membrane electrophysiological properties of stem-like cells is in line with a recent finding from our group showing that cell membrane dielectric properties could potentially be used as a marker for stem cells in neural tissues 39 . With a lack of distinct stem cell markers, isolation of tissuespecific stem cells for tissue engineering and gene therapy is a great challenge.…”
Section: Discussionsupporting
confidence: 87%
“…The change in capacitance could also be related to changes in the permittivity of the membrane due to the action of 4-MU in shortening the HA chains; however, we suggest that of the two mechanisms, the effects of morphology charge are likely to significantly outweigh those of permittivity change. The unique differences in the membrane electrophysiological properties of stem-like cells is in line with a recent finding from our group showing that cell membrane dielectric properties could potentially be used as a marker for stem cells in neural tissues 39 . With a lack of distinct stem cell markers, isolation of tissuespecific stem cells for tissue engineering and gene therapy is a great challenge.…”
Section: Discussionsupporting
confidence: 87%
“…Both cultures express standard neural stem cell markers, including Sox2, nestin, and the cell surface marker CD133, and have the potential to differentiate into the three major neural cell types: astrocytes, neurons, and oligodendrocytes (18)(19)(20)(21)(22). When transplanted into a mouse model of Sandhoff disease, these hNSPCs stably integrated into the host brain and delayed disease onset, reflecting their functional and therapeutic potential (23).…”
Section: Resultsmentioning
confidence: 99%
“…Patch clamp measurements, TIRFM Ca 2+ imaging, and differentiation assays were performed on two brain-derived human fetal hNSPC cultures (SC23 and SC27) isolated from the cerebral cortices of two separate fetuses of 23-wk gestational age (18)(19)(20)(21). Further details on cell-culture conditions, siRNA knockdown experiments, electrophysiological measurements, calcium imaging, Qgel substrate fabrication, and data analysis are presented in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…(2) leads to an accurate measurement of the membrane capacitance. 16 Labeed et al 17 have recently reported that the neurogenic potential of human neural stem/progenitor cell populations can be discriminated by their f xo and derived C m values. On the basis of the efficient DEP-based cell separations reported here, the same conclusion may be reached regarding discrimination between stages of C2C12 myoblast cell differentiation.…”
Section: -1058/2012/6(3)/034113/16/$3000mentioning
confidence: 99%